Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah pada PNM Mekaar: Penelitian - Mira Astika; Zaenal Abidin; Alisyah Pitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Service quality is a key factor in determining customer satisfaction, particularly in non-bank financial institutions with a social mission, such as PT Permodalan Nasional Madani (PNM) Mekaar. This study aims to assess the influence of service quality on customer satisfaction at the Muara Sabak Timur Branch Unit using a descriptive quantitative approach. A sample of 98 respondents was selected from a population of 3,318 customers through disproportionate stratified random sampling. Service quality was analyzed based on the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Customer satisfaction was measured through expectation fulfillment, interest, and the tendency to provide recommendations. The regression analysis results indicate a positive and significant relationship between service quality and customer satisfaction, with a correlation coefficient of 0.647 and a coefficient of determination of 41.9%. These findings underscore the importance of holistically enhancing service quality to strengthen customer loyalty and the effectiveness of sharia-based economic empowerment programs in the ultra-micro sector.